2021
DOI: 10.1103/physrevb.103.l140409
|View full text |Cite
|
Sign up to set email alerts
|

Multiple-magnon excitations shape the spin spectrum of cuprate parent compounds

Abstract: Thanks to high resolution and polarization analysis, resonant inelastic x-ray scattering (RIXS) magnetic spectra of La 2 CuO 4 , Sr 2 CuO 2 C l2 and CaCuO 2 reveal a rich set of properties of the spin-1 /2 antiferromagnetic square lattice of cuprates. The leading single-magnon peak energy dispersion is in excellent agreement with the corresponding inelastic neutron scattering measurements. However, the RIXS data unveil an asymmetric line shape possibly due to odd higher order terms. Moreover, a sharp bimagnon … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 57 publications
(79 reference statements)
1
7
1
Order By: Relevance
“…While this behavior had already been observed in cuprates before [6,7,13], we underline that in the other cuprates the single magnon is anyway the dominant excitation with respect to the continuum (see e.g. [17]). On the contrary, in CaCuO 2 , the single magnon is submerged by a broad and asymmetric continuum and becomes almost undetectable.…”
Section: A Momentum Dependencesupporting
confidence: 65%
See 3 more Smart Citations
“…While this behavior had already been observed in cuprates before [6,7,13], we underline that in the other cuprates the single magnon is anyway the dominant excitation with respect to the continuum (see e.g. [17]). On the contrary, in CaCuO 2 , the single magnon is submerged by a broad and asymmetric continuum and becomes almost undetectable.…”
Section: A Momentum Dependencesupporting
confidence: 65%
“…We have shown that the continuum is not due to the relatively sharp bi-magnon observed for example in S 2 CuO 2 Cl 2 (SCOC) [17], but this does not rule out that it might be due to other types of spin-conserving excitations, i.e., an incoherent continuum of two magnons. To truly determine its nature, we performed RIXS measurements with polarization analysis on the scattered beam [38][39][40].…”
Section: B Polarimetric Measurementsmentioning
confidence: 71%
See 2 more Smart Citations
“…Here, the presence of a core-hole in the intermediate state allows for a diverse set of scattering channels including both spin-conserving (SC, ∆S tot = 0) and non-spin-conserving (NSC, ∆S tot = 1) processes. The RIXS intensity can only be directly equated with the dynamical structure factors under certain scattering conditions [22] or in the limit of ultrashort core-hole lifetimes [23], a fact that is becoming more evident with the recent developments in resolving the polarization of the scattered x-rays [11,24,25]. While this aspect complicates the interpretation of RIXS experiments, it has also led to the observation of novel excitations such as orbitons [26,27] and SC four-spinon excitations outside two-spinon phase space [28,29] in the onedimensional (1D) Heisenberg antiferromagnetic (HAFM) spin chain Sr 2 CuO 3 .…”
mentioning
confidence: 99%